Pengaruh Puree Labu Kuning (Cucurbita moschata D.) Terhadap Karakteristik Brownies Tepung Ketan Hitam (Oryza sativa L.var.glutinosa) - Sholin, Iis; Suparthana, Putu; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This study aimed to determine the effect of yellow pumpkin puree to the characteristics of brownies which made by black glutinous rice flour, and to find out the preeminent characteristics. The experiment was designed as a completely randomized design with 5 level treatments (0%, 10%, 20%, 30%, and 40%) of yellow pumpkin puree addition. The treatment was repeated for 3 times to obtain 15 experimental unit overall. The data was analyzed by using analysis of variance tool (ANOVA) and continued with Duncan Multiple Range Test (DMRT) for the data showing significant effect. The result showed that addition of yellow pumpkin puree to brownies had a significant effect on water content, ash content, ?-carotene, antioxidant activity of ?-carotene bleaching, hedonic test (color, flavour, texture, taste, and overall acceptance) and score test for texture. The 40% addition of yellow pumpkin puree to brownies made by black glutinous rice flour, giving the preeminent characteristics with 1.32% of ash content, 37.73% of water content, 6.82 mg/100g of ?- carotene, and 1.72% of ?-carotene bleaching. Hedonic scale was “like” for color, flavour, taste and overall acceptance, and considerably soft texture as determined by score test.